10 principles for an innovative model for the 21st century university: the «educational campus» - Pablo CAMPOS CALVO-SOTELO (Ediciones Universidad de Salamanca, 2010)
University education has a higher purpose - to reinforce the formation of human beings and to provide the individual with an overall integrated training. This mission necessitates giving special attention to the correct arrangement of the physical space in which this central undertaking occurs.